Enterprise: Creation, Development and Growth (Malaysian Management Journal, 1992)
The subject of this book is divided into twelve chapters with the first chapter starting with an overview of the enterprise concept. This chapter also highlights how individuals show enterprise in many situations. The remaining chapters cover the spread of ideas such as the entrepreneurial economy, enterprise support system, building and managing an enterprise, management and the larger enterprise, public and voluntary enterprises, personal development, group work and networking. Finally, there is a chapter on individuality, enterprise and the future.